The Students’ Writing Anxiety at The Fourth Semester Students in Academic Writing Class - Paramarti, Prajna Fawwaza Alya; Tusino, Tusino; Widodo, Sri; Masykuri, Edi Sunjayanto (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2023)
The purpose of this study was to find out how much writing anxiety exists among students, what causes it, and how to deal with it in academic writing courses. This research uses qualitative. This study was done at Universitas Muhammadiyah Purworejo using fourth-semester students who took an academic writing course as subjects. The findings revealed that the students' writing anxiety was in the high range (67.23).